Preparation method of BOPET (Biaxially Oriented Polyethylene Terephthalate) film for composite current collector
By adding graphene to the core layer of the BOPET film, and using nano-SiO2 and nano-CaCO3 modified anti-stick masterbatch and water-based epoxy coating liquid on the surface, the problem of low high-temperature cycles and rapid capacity decline of the PET substrate is solved. problem, achieving higher conductivity efficiency, mechanical strength and heat resistance, and enhancing corrosion resistance.
Patent Information
- Application Number
- CN202411443105.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-10-16
AI Technical Summary
The problem of low cycle times and rapid capacity decline at high temperatures is that PET substrates are seriously corroded due to coating defects in battery cells, which affects the industrialization process.
Adopt a composite set of flowers with a BOPET film preparation method. By adding graphene to the film core layer for co -mixed modification, combined with nano SiO2 and nano CACO3 modified anti -sticking mother materials as the functional layer, and coat the water on the surface online water -based epoxy oxygen The coating solution is used to improve corrosion resistance.
A significant reduction of the resistance of the film, improved the performance and mechanical performance of the conductivity, enhanced the heat resistance and corrosion resistance, and extended the service life of the battery.
Smart Images

Figure BDA0005086895590000201 
Figure BDA0005086895590000211
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of BOPET films, and in particular to a method for preparing a BOPET film for a composite current collector. Background Art
[0002] At present, PET / PP is the mainstream material for composite current collector substrates. Among them, PET has a faster pace of industrialization due to its outstanding mechanical properties and coating advantages, and has reached the initial mass production stage. However, the finished battery cells based on PET substrates have problems with low high-temperature cycles and fast capacity decay during testing and use. The reason is that the pinholes on the surface of the composite current collector due to coating defects expose the PET substrate, which cannot resist the corrosion of the electrolyte under long-term high temperature conditions, resulting in battery capacity loss over time. In particular, the negative electrode has a low oxidation potential, and unlike the positive electrode, it has a dense aluminum oxide layer for protection, so the corrosion problem is more serious, which greatly affects the industrialization process of PET copper foil. At the same time, based on the battery manufacturing process and operating conditions, PET materials have always had essential differences in mechanical properties, electrical conductivity and thermal stability compared to traditional pure metals, which is reflected in the production and use of coating broken belts, foil wrinkles and low battery rate problems, which increase product quality risks. Therefore, in order to better replace traditional foils and apply them to the field of current collectors, it is urgent to explore a method to improve the performance and corrosion resistance of PET films. Summary of the invention
[0003] In order to make the BOPET film corrosion-resistant and better suitable for the application environment of battery current collectors, the present invention describes a method for preparing a BOPET film for a composite current collector, which has the following steps:
[0004] A BOPET film for a composite current collector comprises, from top to bottom:
[0005] An upper surface layer, a core layer and a lower surface layer; and also includes a water-based epoxy coating liquid coated on the upper and lower surfaces of the film;
[0006] The upper surface layer comprises: bright polyester chips, nano-SiO2 modified anti-sticking masterbatch, nano-CaCO3 modified anti-sticking masterbatch; the raw materials of the core layer comprise: graphene modified bright polyester chips; the lower surface layer comprises: bright polyester chips, nano-SiO2 modified anti-sticking masterbatch, nano-CaCO3 modified anti-sticking masterbatch.
[0007] Preferably, the graphene-modified high-gloss polyester chips include nanographene materials and polyethylene terephthalate.
[0008] Preferably, the nano-CaCO3 modified anti-sticking masterbatch comprises nano-CaCO3 particles, terephthalic acid, isophthalic acid and ethylene glycol.
[0009] Preferably, the nano-SiO2 modified anti-sticking masterbatch comprises nano-SiO2 particles, terephthalic acid, isophthalic acid and ethylene glycol.
[0010] Preferably, the mass fraction of the glossy polyester chips in the upper surface layer and the lower surface layer is 60%.
[0011] Preferably, the mass fraction of the nano-SiO2 modified anti-sticking masterbatch in the upper surface layer and the lower surface layer is 20%.
[0012] Preferably, the mass fraction of the nano-CaCO3 modified anti-sticking masterbatch in the upper surface layer and the lower surface layer is 20%.
[0013] Preferably, the water-based epoxy coating liquid comprises water-based epoxy emulsion, water-based silica sol, a defoaming agent and a leveling agent.
[0014] A method for preparing a BOPET film for a composite current collector, the method comprising the following steps:
[0015] Deionized water is added to the water-based epoxy emulsion, and the mixture is stirred. Meanwhile, water-based silica sol, defoamer and leveling agent are added thereto, and the mixture is stirred. Finally, a curing agent is added and mixed to obtain a water-based epoxy coating liquid.
[0016] The core layer raw material is pre-crystallized, air-dried, impurity-removed, melted, extruded to the filter screen, and finally transported to the die head; the upper surface layer raw material is melted and extruded, and the melt is vacuum-dried at the same time, and then transported to the die head; the lower surface layer and the upper surface layer share a single screw extruder, and are transported to each surface layer at the die head through a splitter;
[0017] The core layer, upper surface layer and lower surface layer melts are conveyed to the three-layer die head through the melt pipe and accurately measured by the melt pump, and then cast and attached to the surface of the cold roller under the action of static electricity to form a polyester thick sheet with an upper surface layer, a core layer and a lower surface layer;
[0018] After the thick sheet is longitudinally stretched, it is subjected to double-sided corona treatment, and then the water-based epoxy coating liquid is coated on both sides of the film online, and then enters the transverse stretching section for preheating, stretching, shaping and cooling treatment in sequence;
[0019] The final formed film enters the traction section for flattening, thickness measurement, trimming and collection into a mother roll, and then is slit to produce the finished film.
[0020] Application of the above-mentioned BOPET film for composite current collector or the BOPET film for composite current collector prepared by the above-mentioned preparation method in manufacturing battery cells.
[0021] The present invention proposes a method for preparing a BOPET film for a composite current collector. The method has the following significant advantages: by adding graphene to the PET slices in the core layer of the film for blending and modification, the resistivity of the film as a whole can be significantly reduced, so that the obtained composite current collector has better conductivity. The surface layer A and the surface layer C use anti-sticking masterbatch (CaCO3 / SiO2) modified with different additives, and are mixed in a specific ratio as the functional layer of the film. Due to the characteristics of high specific surface area and surface activation energy of nano-CaCO3, when the PET matrix is heated, it can effectively absorb the heat energy in the PET molecules, and the CaCO3 interspersed in the PET molecular chain segment can further hinder the movement of the chain segment, increase the resin melting peak, and improve the overall thermal shrinkage of the film; and nano-SiO2, as a heterogeneous nucleating agent, can affect the crystallization behavior of PET molecules, especially at high temperatures, it can promote the formation of polymer molecules lattices and improve the overall mechanical properties of the film. Finally, by coating a dense epoxy resin anti-corrosion layer on the surface of the film, the surface of the film becomes chemically inert, blocking the contact corrosion of the electrolyte. In addition, due to the rich polar groups on the surface of the epoxy resin, it is more conducive to the adhesion of the metal foil to the surface of the base film.
[0022] The BOPET film prepared by the present invention has higher conductivity efficiency, more excellent mechanical strength and heat resistance, and further has corrosion resistance through online coating of anti-corrosion coating, which not only ensures the quality of subsequent composite current collector processing, but also avoids the capacity loss of the manufactured battery cell due to electrolyte corrosion, reaching the level of traditional battery cells. DETAILED DESCRIPTION
[0023] The technical solutions in the embodiments of the present invention are described clearly and completely. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] The present invention provides a method for preparing a BOPET film for a composite current collector. The present invention will be further described below in conjunction with specific implementation examples, but the present invention is not limited to the following implementation examples.
[0025] In the following examples and comparative examples, the raw materials used to prepare the BOPET film include high-gloss polyester chips, graphene-modified polyester chips ① (effective ingredient: 5 nm, 1.2%), graphene-modified polyester chips ② (effective ingredient: 2 nm, 2.5%), graphene-modified polyester chips ③ (effective ingredient: 10 nm, 0.5%), nano-SiO2 modified anti-sticking masterbatch (effective ingredient: 0.6 μm, 2%), nano-CaCO3 modified anti-sticking masterbatch (effective ingredient: 0.6 μm, 2%), and graphene-modified polyester chips ③ (effective ingredient: 10 nm, 0.5%). :~0.65μm, 1.5%), commercial anti-sticking masterbatch K (SiO2, 3.0μm, 3300ppm), commercial anti-sticking masterbatch S (CaCO3, 3.5μm, 3300ppm), wherein the graphene-modified polyester chips are made by melt blending of nano-graphene materials and polyethylene terephthalate, and the CaCO3 / SiO2 modified masterbatch is made by mixing various additives with terephthalic acid, isophthalic acid and ethylene glycol, and then undergoing esterification and polycondensation.
[0026] Example 1
[0027] Example 1 describes a method for preparing a BOPET film for a composite current collector, and the specific steps include:
[0028] (1) Preparation of water-based epoxy coating liquid
[0029] Add 20 parts by weight of water-based epoxy emulsion K-020 into a mixing tank, add 75 parts by weight of deionized water, stir at 500 rpm, and continue to add 2 parts by weight of water-based silica sol LS-50, 0.5 parts by weight of defoamer BW-225 and 0.5 parts by weight of leveling agent BW-404, continue stirring for 30 minutes, and finally add 2 parts by weight of curing agent K-62 and mix thoroughly to obtain a water-based epoxy coating liquid.
[0030] (2) Preparation of online coated BOPET film
[0031] The BOPET film in this embodiment is a typical three-layer co-extruded polyester film, wherein the A layer (upper surface layer) contains bright polyester chips, nano-SiO2 modified anti-sticking masterbatch and nano-CaCO3 modified anti-sticking masterbatch, wherein the mass fraction of the bright polyester chips is 60%, the mass fraction of the nano-SiO2 modified anti-sticking masterbatch is 20%, and the mass fraction of the nano-CaCO3 modified anti-sticking masterbatch is 20%; the B layer (core layer) contains graphene-modified bright polyester chips①; the C layer (lower surface layer) contains bright polyester chips, nano-SiO2 modified anti-sticking masterbatch and nano-CaCO3 modified anti-sticking masterbatch, wherein the mass fraction of the bright polyester chips is 60%, the mass fraction of the nano-SiO2 modified anti-sticking masterbatch is 20%, and the mass fraction of the nano-CaCO3 modified anti-sticking masterbatch is 20%.
[0032] After pre-crystallization at 165°C, the raw material of layer B is sent to a fluidized bed and a drying tower for blast drying and impurity removal, and then enters a single-screw extruder 1, melted at 275°C, extruded onto a filter screen, and finally transported to a die head after metering by a melt pump; the raw material of layer A is directly sent to a single-screw extruder 2, melted and extruded at 280°C, and the melt is vacuum dried to remove moisture, and then transported to a die head after metering by a filter screen and a melt pump; layer C and layer A share a single-screw extruder 2, and are respectively transported to each surface layer at the die head through a diverter.
[0033] The melts of each layer are gathered at the die head to form a three-layer molten film sheet, which is slowly and evenly cast from the film lip. At the same time, under the action of 6.8kV high-voltage static electricity, it is tightly attached to the surface of a 29°C cold roller and cast into a thick polyester sheet.
[0034] The obtained thick sheet was passed to the longitudinal stretching section and longitudinally stretched under the conditions of preheating temperature of 85°C, stretching temperature of 101°C, and stretching ratio of 3.1. Then, the A and C sides of the export film were corona treated in turn, and then a uniform layer of water-based epoxy coating liquid was coated on both sides of the film through an anilox roller online coating device, with a coating amount of 2.5g / m on each side. 2 Then the film enters the transverse stretching section and is transversely stretched under the conditions of preheating temperature 90°C, stretching temperature 105°C, setting temperature 225°C, and stretching ratio 3.2, and is cooled at 25°C to obtain a biaxially stretched polyester film.
[0035] The final formed film enters the traction section for flattening, thickness measurement, trimming and collection into a mother roll, and then is slit to produce the finished film.
[0036] Example 2
[0037] Example 2 describes a method for preparing a BOPET film for a composite current collector, and the specific steps include (compared with Example 1, the type of B-layer graphene-modified polyester slice is changed):
[0038] (1) Preparation of water-based epoxy coating liquid
[0039] Add 20 parts by weight of water-based epoxy emulsion K-020 into a mixing tank, add 75 parts by weight of deionized water, stir at 500 rpm, and continue to add 2 parts by weight of water-based silica sol LS-50, 0.5 parts by weight of defoamer BW-225 and 0.5 parts by weight of leveling agent BW-404, continue stirring for 30 minutes, and finally add 2 parts by weight of curing agent K-62 and mix thoroughly to obtain a water-based epoxy coating liquid.
[0040] (2) Preparation of online coated BOPET film
[0041] The BOPET film in this embodiment is a typical three-layer co-extruded polyester film, wherein the A layer (upper surface layer) contains bright polyester chips, nano-SiO2 modified anti-sticking masterbatch and nano-CaCO3 modified anti-sticking masterbatch, wherein the mass fraction of the bright polyester chips is 60%, the mass fraction of the nano-SiO2 modified anti-sticking masterbatch is 20%, and the mass fraction of the nano-CaCO3 modified anti-sticking masterbatch is 20%; the B layer (core layer) contains graphene-modified bright polyester chips②; the C layer (lower surface layer) contains bright polyester chips, nano-SiO2 modified anti-sticking masterbatch and nano-CaCO3 modified anti-sticking masterbatch, wherein the mass fraction of the bright polyester chips is 60%, the mass fraction of the nano-SiO2 modified anti-sticking masterbatch is 20%, and the mass fraction of the nano-CaCO3 modified anti-sticking masterbatch is 20%.
[0042] After pre-crystallization at 165°C, the raw material of layer B is sent to a fluidized bed and a drying tower for blast drying and impurity removal, and then enters a single-screw extruder 1, melted at 275°C, extruded onto a filter screen, and finally transported to a die head after metering by a melt pump; the raw material of layer A is directly sent to a single-screw extruder 2, melted and extruded at 280°C, and the melt is vacuum dried to remove moisture, and then transported to a die head after metering by a filter screen and a melt pump; layer C and layer A share a single-screw extruder 2, and are respectively transported to each surface layer at the die head through a diverter.
[0043] The melts of each layer are gathered at the die head to form a three-layer molten film sheet, which is slowly and evenly cast from the film lip. At the same time, under the action of 6.8kV high-voltage static electricity, it is tightly attached to the surface of a 29°C cold roller and cast into a thick polyester sheet.
[0044] The obtained thick sheet was passed to the longitudinal stretching section and longitudinally stretched under the conditions of preheating temperature of 85°C, stretching temperature of 101°C, and stretching ratio of 3.1. Then, the A and C sides of the export film were corona treated in turn, and then a uniform layer of water-based epoxy coating liquid was coated on both sides of the film through an anilox roller online coating device, with a coating amount of 2.5g / m on each side. 2 Then the film enters the transverse stretching section and is transversely stretched under the conditions of preheating temperature 90°C, stretching temperature 105°C, setting temperature 225°C, and stretching ratio 3.2, and is cooled at 25°C to obtain a biaxially stretched polyester film.
[0045] The final formed film enters the traction section for flattening, thickness measurement, trimming and collection into a mother roll, and then is slit to produce the finished film.
[0046] Example 3
[0047] Example 3 describes a method for preparing a BOPET film for a composite current collector, and the specific steps include: (Compared with Example 1, the type of B-layer graphene-modified polyester slice is changed)
[0048] (1) Preparation of water-based epoxy coating liquid
[0049] Add 20 parts by weight of water-based epoxy emulsion K-020 into a mixing tank, add 75 parts by weight of deionized water, stir at 500 rpm, and continue to add 2 parts by weight of water-based silica sol LS-50, 0.5 parts by weight of defoamer BW-225 and 0.5 parts by weight of leveling agent BW-404, continue stirring for 30 minutes, and finally add 2 parts by weight of curing agent K-62 and mix thoroughly to obtain a water-based epoxy coating liquid.
[0050] (2) Preparation of online coated BOPET film
[0051] The BOPET film in this embodiment is a typical three-layer co-extruded polyester film, wherein the A layer (upper surface layer) contains bright polyester chips, nano-SiO2 modified anti-sticking masterbatch and nano-CaCO3 modified anti-sticking masterbatch, wherein the mass fraction of the bright polyester chips is 60%, the mass fraction of the nano-SiO2 modified anti-sticking masterbatch is 20%, and the mass fraction of the nano-CaCO3 modified anti-sticking masterbatch is 20%; the B layer (core layer) contains graphene-modified bright polyester chips ③; the C layer (lower surface layer) contains bright polyester chips, nano-SiO2 modified anti-sticking masterbatch and nano-CaCO3 modified anti-sticking masterbatch, wherein the mass fraction of the bright polyester chips is 60%, the mass fraction of the nano-SiO2 modified anti-sticking masterbatch is 20%, and the mass fraction of the nano-CaCO3 modified anti-sticking masterbatch is 20%.
[0052] After pre-crystallization at 165°C, the raw material of layer B is sent to a fluidized bed and a drying tower for blast drying and impurity removal, and then enters a single-screw extruder 1, melted at 275°C, extruded onto a filter screen, and finally transported to a die head after metering by a melt pump; the raw material of layer A is directly sent to a single-screw extruder 2, melted and extruded at 280°C, and the melt is vacuum dried to remove moisture, and then transported to a die head after metering by a filter screen and a melt pump; layer C and layer A share a single-screw extruder 2, and are respectively transported to each surface layer at the die head through a diverter.
[0053] The melts of each layer are gathered at the die head to form a three-layer molten film sheet, which is slowly and evenly cast from the film lip. At the same time, under the action of 6.8kV high-voltage static electricity, it is tightly attached to the surface of a 29°C cold roller and cast into a thick polyester sheet.
[0054] The obtained thick sheet was passed to the longitudinal stretching section and longitudinally stretched under the conditions of preheating temperature of 85°C, stretching temperature of 101°C, and stretching ratio of 3.1. Then, the A and C sides of the export film were corona treated in turn, and then a uniform layer of water-based epoxy coating liquid was coated on both sides of the film through an anilox roller online coating device, with a coating amount of 2.5g / m on each side. 2Then the film enters the transverse stretching section and is transversely stretched under the conditions of preheating temperature 90°C, stretching temperature 105°C, setting temperature 225°C, and stretching ratio 3.2, and is cooled at 25°C to obtain a biaxially stretched polyester film.
[0055] The final formed film enters the traction section for flattening, thickness measurement, trimming and collection into a mother roll, and then is slit to produce the finished film.
[0056] Example 4
[0057] Example 4 describes a method for preparing a BOPET film for a composite current collector, and the specific steps include: (Compared with Example 1, the ratio of the water-based epoxy coating liquid is changed)
[0058] (1) Preparation of water-based epoxy coating liquid
[0059] Add 15 parts by mass of water-based epoxy emulsion K-020 into a mixing tank, add 81.4 parts by mass of deionized water, stir at 500 rpm, and continue to add 1.5 parts by mass of water-based silica sol LS-50, 0.3 parts by mass of defoamer BW-225 and 0.3 parts by mass of leveling agent BW-404, continue stirring for 30 minutes, and finally add 1.5 parts by mass of curing agent K-62 and mix thoroughly to obtain a water-based epoxy coating liquid.
[0060] (2) Preparation of online coated BOPET film
[0061] The BOPET film in this embodiment is a typical three-layer co-extruded polyester film, wherein the A layer (upper surface layer) contains bright polyester chips, nano-SiO2 modified anti-sticking masterbatch and nano-CaCO3 modified anti-sticking masterbatch, wherein the mass fraction of the bright polyester chips is 60%, the mass fraction of the nano-SiO2 modified anti-sticking masterbatch is 20%, and the mass fraction of the nano-CaCO3 modified anti-sticking masterbatch is 20%; the B layer (core layer) contains graphene-modified bright polyester chips①; the C layer (lower surface layer) contains bright polyester chips, nano-SiO2 modified anti-sticking masterbatch and nano-CaCO3 modified anti-sticking masterbatch, wherein the mass fraction of the bright polyester chips is 60%, the mass fraction of the nano-SiO2 modified anti-sticking masterbatch is 20%, and the mass fraction of the nano-CaCO3 modified anti-sticking masterbatch is 20%.
[0062] After pre-crystallization at 165°C, the raw material of layer B is sent to a fluidized bed and a drying tower for blast drying and impurity removal, and then enters a single-screw extruder 1, melted at 275°C, extruded onto a filter screen, and finally transported to a die head after metering by a melt pump; the raw material of layer A is directly sent to a single-screw extruder 2, melted and extruded at 280°C, and the melt is vacuum dried to remove moisture, and then transported to a die head after metering by a filter screen and a melt pump; layer C and layer A share a single-screw extruder 2, and are respectively transported to each surface layer at the die head through a diverter.
[0063] The melts of each layer are gathered at the die head to form a three-layer molten film sheet, which is slowly and evenly cast from the film lip. At the same time, under the action of 6.8kV high-voltage static electricity, it is tightly attached to the surface of a 29°C cold roller and cast into a thick polyester sheet.
[0064] The obtained thick sheet was passed to the longitudinal stretching section and longitudinally stretched under the conditions of preheating temperature of 85°C, stretching temperature of 101°C, and stretching ratio of 3.1. Then, the A and C sides of the export film were corona treated in turn, and then a uniform layer of water-based epoxy coating liquid was coated on both sides of the film through an anilox roller online coating device, with a coating amount of 2.5g / m on each side. 2 Then the film enters the transverse stretching section and is transversely stretched under the conditions of preheating temperature 90°C, stretching temperature 105°C, setting temperature 225°C, and stretching ratio 3.2, and is cooled at 25°C to obtain a biaxially stretched polyester film.
[0065] The final formed film enters the traction section for flattening, thickness measurement, trimming and collection into a mother roll, and then is slit to produce the finished film.
[0066] Example 5
[0067] Example 5 describes a method for preparing a BOPET film for a composite current collector, and the specific steps include: (Compared with Example 1, the ratio of the water-based epoxy coating liquid is changed)
[0068] (1) Preparation of water-based epoxy coating liquid
[0069] Add 25 parts by mass of water-based epoxy emulsion K-020 into a mixing tank, add 68.6 parts by mass of deionized water, stir at 500 rpm, and continue to add 2.5 parts by mass of water-based silica sol LS-50, 0.7 parts by mass of defoamer BW-225 and 0.7 parts by mass of leveling agent BW-404, continue stirring for 30 minutes, and finally add 2.5 parts by mass of curing agent K-62 and mix thoroughly to obtain a water-based epoxy coating liquid.
[0070] (2) Preparation of online coated BOPET film
[0071] The BOPET film in this embodiment is a typical three-layer co-extruded polyester film, wherein the A layer (upper surface layer) contains bright polyester chips, nano-SiO2 modified anti-sticking masterbatch and nano-CaCO3 modified anti-sticking masterbatch, wherein the mass fraction of the bright polyester chips is 60%, the mass fraction of the nano-SiO2 modified anti-sticking masterbatch is 20%, and the mass fraction of the nano-CaCO3 modified anti-sticking masterbatch is 20%; the B layer (core layer) contains graphene-modified bright polyester chips①; the C layer (lower surface layer) contains bright polyester chips, nano-SiO2 modified anti-sticking masterbatch and nano-CaCO3 modified anti-sticking masterbatch, wherein the mass fraction of the bright polyester chips is 60%, the mass fraction of the nano-SiO2 modified anti-sticking masterbatch is 20%, and the mass fraction of the nano-CaCO3 modified anti-sticking masterbatch is 20%.
[0072] After pre-crystallization at 165°C, the raw material of layer B is sent to a fluidized bed and a drying tower for blast drying and impurity removal, and then enters a single-screw extruder 1, melted at 275°C, extruded onto a filter screen, and finally transported to a die head after metering by a melt pump; the raw material of layer A is directly sent to a single-screw extruder 2, melted and extruded at 280°C, and the melt is vacuum dried to remove moisture, and then transported to a die head after metering by a filter screen and a melt pump; layer C and layer A share a single-screw extruder 2, and are respectively transported to each surface layer at the die head through a diverter.
[0073] The melts of each layer are gathered at the die head to form a three-layer molten film sheet, which is slowly and evenly cast from the film lip. At the same time, under the action of 6.8kV high-voltage static electricity, it is tightly attached to the surface of a 29°C cold roller and cast into a thick polyester sheet.
[0074] The obtained thick sheet was passed to the longitudinal stretching section and longitudinally stretched under the conditions of preheating temperature of 85°C, stretching temperature of 101°C, and stretching ratio of 3.1. Then, the A and C sides of the export film were corona treated in turn, and then a uniform layer of water-based epoxy coating liquid was coated on both sides of the film through an anilox roller online coating device, with a coating amount of 2.5g / m on each side. 2 Then the film enters the transverse stretching section and is transversely stretched under the conditions of preheating temperature 90°C, stretching temperature 105°C, setting temperature 225°C, and stretching ratio 3.2, and is cooled at 25°C to obtain a biaxially stretched polyester film.
[0075] The final formed film enters the traction section for flattening, thickness measurement, trimming and collection into a mother roll, and then is slit to produce the finished film.
[0076] Example 6
[0077] Example 6 describes a method for preparing a BOPET film for a composite current collector, and the specific steps include: (Compared with Example 1, the A / C layer raw material ratio is changed)
[0078] (1) Preparation of water-based epoxy coating liquid
[0079] Add 20 parts by weight of water-based epoxy emulsion K-020 into a mixing tank, add 75 parts by weight of deionized water, stir at 500 rpm, and continue to add 2 parts by weight of water-based silica sol LS-50, 0.5 parts by weight of defoamer BW-225 and 0.5 parts by weight of leveling agent BW-404, continue stirring for 30 minutes, and finally add 2 parts by weight of curing agent K-62 and mix thoroughly to obtain a water-based epoxy coating liquid.
[0080] (2) Preparation of online coated BOPET film
[0081] The BOPET film in this embodiment is a typical three-layer co-extruded polyester film, wherein the A layer (upper surface layer) contains bright polyester chips, nano-SiO2 modified anti-sticking masterbatch and nano-CaCO3 modified anti-sticking masterbatch, wherein the mass fraction of the bright polyester chips is 70%, the mass fraction of the nano-SiO2 modified anti-sticking masterbatch is 15%, and the mass fraction of the nano-CaCO3 modified anti-sticking masterbatch is 15%; the B layer (core layer) contains graphene-modified bright polyester chips①; the C layer (lower surface layer) contains bright polyester chips, nano-SiO2 modified anti-sticking masterbatch and nano-CaCO3 modified anti-sticking masterbatch, wherein the mass fraction of the bright polyester chips is 70%, the mass fraction of the nano-SiO2 modified anti-sticking masterbatch is 15%, and the mass fraction of the nano-CaCO3 modified anti-sticking masterbatch is 15%.
[0082] After pre-crystallization at 165°C, the raw material of layer B is sent to a fluidized bed and a drying tower for blast drying and impurity removal, and then enters a single-screw extruder 1, melted at 275°C, extruded onto a filter screen, and finally transported to a die head after metering by a melt pump; the raw material of layer A is directly sent to a single-screw extruder 2, melted and extruded at 280°C, and the melt is vacuum dried to remove moisture, and then transported to a die head after metering by a filter screen and a melt pump; layer C and layer A share a single-screw extruder 2, and are respectively transported to each surface layer at the die head through a diverter.
[0083] The melts of each layer are gathered at the die head to form a three-layer molten film sheet, which is slowly and evenly cast from the film lip. At the same time, under the action of 6.8kV high-voltage static electricity, it is tightly attached to the surface of a 29°C cold roller and cast into a thick polyester sheet.
[0084] The obtained thick sheet was passed to the longitudinal stretching section and longitudinally stretched under the conditions of preheating temperature of 85°C, stretching temperature of 101°C, and stretching ratio of 3.1. Then, the A and C sides of the export film were corona treated in turn, and then a uniform layer of water-based epoxy coating liquid was coated on both sides of the film through an anilox roller online coating device, with a coating amount of 2.5g / m on each side. 2Then the film enters the transverse stretching section and is transversely stretched under the conditions of preheating temperature 90°C, stretching temperature 105°C, setting temperature 225°C, and stretching ratio 3.2, and is cooled at 25°C to obtain a biaxially stretched polyester film.
[0085] The final formed film enters the traction section for flattening, thickness measurement, trimming and collection into a mother roll, and then is slit to produce the finished film.
[0086] Example 7
[0087] Example 7 describes a method for preparing a BOPET film for a composite current collector, and the specific steps include: (Compared with Example 1, the A / C layer raw material ratio is changed)
[0088] (1) Preparation of water-based epoxy coating liquid
[0089] Add 20 parts by weight of water-based epoxy emulsion K-020 into a mixing tank, add 75 parts by weight of deionized water, stir at 500 rpm, and continue to add 2 parts by weight of water-based silica sol LS-50, 0.5 parts by weight of defoamer BW-225 and 0.5 parts by weight of leveling agent BW-404, continue stirring for 30 minutes, and finally add 2 parts by weight of curing agent K-62 and mix thoroughly to obtain a water-based epoxy coating liquid.
[0090] (2) Preparation of online coated BOPET film
[0091] The BOPET film in this embodiment is a typical three-layer co-extruded polyester film, wherein the A layer (upper surface layer) contains bright polyester chips, nano-SiO2 modified anti-sticking masterbatch and nano-CaCO3 modified anti-sticking masterbatch, wherein the mass fraction of the bright polyester chips is 50%, the mass fraction of the nano-SiO2 modified anti-sticking masterbatch is 25%, and the mass fraction of the nano-CaCO3 modified anti-sticking masterbatch is 25%; the B layer (core layer) contains graphene-modified bright polyester chips①; the C layer (lower surface layer) contains bright polyester chips, nano-SiO2 modified anti-sticking masterbatch and nano-CaCO3 modified anti-sticking masterbatch, wherein the mass fraction of the bright polyester chips is 50%, the mass fraction of the nano-SiO2 modified anti-sticking masterbatch is 25%, and the mass fraction of the nano-CaCO3 modified anti-sticking masterbatch is 25%.
[0092] After pre-crystallization at 165°C, the raw material of layer B is sent to a fluidized bed and a drying tower for blast drying and impurity removal, and then enters a single-screw extruder 1, melted at 275°C, extruded onto a filter screen, and finally transported to a die head after metering by a melt pump; the raw material of layer A is directly sent to a single-screw extruder 2, melted and extruded at 280°C, and the melt is vacuum dried to remove moisture, and then transported to a die head after metering by a filter screen and a melt pump; layer C and layer A share a single-screw extruder 2, and are respectively transported to each surface layer at the die head through a diverter.
[0093] The melts of each layer are gathered at the die head to form a three-layer molten film sheet, which is slowly and evenly cast from the film lip. At the same time, under the action of 6.8kV high-voltage static electricity, it is tightly attached to the surface of a 29°C cold roller and cast into a thick polyester sheet.
[0094] The obtained thick sheet was passed to the longitudinal stretching section and longitudinally stretched under the conditions of preheating temperature of 85°C, stretching temperature of 101°C, and stretching ratio of 3.1. Then, the A and C sides of the export film were corona treated in turn, and then a uniform layer of water-based epoxy coating liquid was coated on both sides of the film through an anilox roller online coating device, with a coating amount of 2.5g / m on each side. 2 Then the film enters the transverse stretching section and is transversely stretched under the conditions of preheating temperature 90°C, stretching temperature 105°C, setting temperature 225°C, and stretching ratio 3.2, and is cooled at 25°C to obtain a biaxially stretched polyester film.
[0095] The final formed film enters the traction section for flattening, thickness measurement, trimming and collection into a mother roll, and then is slit to produce the finished film.
[0096] Comparative Example 1
[0097] Comparative Example 1 describes a method for preparing a BOPET film for a composite current collector, and the specific steps include: (Compared with Example 1, the film is not coated with an anti-corrosion functional layer)
[0098] (1) Preparation of non-online coated BOPET film
[0099] The BOPET film in this embodiment is a typical three-layer co-extruded polyester film, wherein the A layer (upper surface layer) contains bright polyester chips, nano-SiO2 modified anti-sticking masterbatch and nano-CaCO3 modified anti-sticking masterbatch, wherein the mass fraction of the bright polyester chips is 60%, the mass fraction of the nano-SiO2 modified anti-sticking masterbatch is 20%, and the mass fraction of the nano-CaCO3 modified anti-sticking masterbatch is 20%; the B layer (core layer) contains graphene-modified bright polyester chips①; the C layer (lower surface layer) contains bright polyester chips, nano-SiO2 modified anti-sticking masterbatch and nano-CaCO3 modified anti-sticking masterbatch, wherein the mass fraction of the bright polyester chips is 60%, the mass fraction of the nano-SiO2 modified anti-sticking masterbatch is 20%, and the mass fraction of the nano-CaCO3 modified anti-sticking masterbatch is 20%.
[0100] After pre-crystallization at 165°C, the raw material of layer B is sent to a fluidized bed and a drying tower for blast drying and impurity removal, and then enters a single-screw extruder 1, melted at 275°C, extruded onto a filter screen, and finally transported to a die head after metering by a melt pump; the raw material of layer A is directly sent to a single-screw extruder 2, melted and extruded at 280°C, and the melt is vacuum dried to remove moisture, and then transported to a die head after metering by a filter screen and a melt pump; layer C and layer A share a single-screw extruder 2, and are respectively transported to each surface layer at the die head through a diverter.
[0101] The melts of each layer are gathered at the die head to form a three-layer molten film sheet, which is slowly and evenly cast from the film lip. At the same time, under the action of 6.8kV high-voltage static electricity, it is tightly attached to the surface of a 29°C cold roller and cast into a thick polyester sheet.
[0102] The obtained thick sheet was passed to the longitudinal stretching section and longitudinally stretched under the conditions of preheating temperature of 85°C, stretching temperature of 101°C, and stretching ratio of 3.1. Then, the A and C sides of the export film were corona treated in turn, and then a uniform layer of water-based epoxy coating liquid was coated on both sides of the film through an anilox roller online coating device, with a coating amount of 2.5g / m on each side. 2 Then the film enters the transverse stretching section and is transversely stretched under the conditions of preheating temperature 90°C, stretching temperature 105°C, setting temperature 225°C, and stretching ratio 3.2, and is cooled at 25°C to obtain a biaxially stretched polyester film.
[0103] The final formed film enters the traction section for flattening, thickness measurement, trimming and collection into a mother roll, and then is slit to produce the finished film.
[0104] Comparative Example 2
[0105] Comparative Example 2 describes a method for preparing a BOPET film for a composite current collector, and the specific steps include: (Compared with Example 1, the raw material of the film B layer is changed)
[0106] (1) Preparation of water-based epoxy coating liquid
[0107] Add 20 parts by weight of water-based epoxy emulsion K-020 into a mixing tank, add 75 parts by weight of deionized water, stir at 500 rpm, and continue to add 2 parts by weight of water-based silica sol LS-50, 0.5 parts by weight of defoamer BW-225 and 0.5 parts by weight of leveling agent BW-404, continue stirring for 30 minutes, and finally add 2 parts by weight of curing agent K-62 and mix thoroughly to obtain a water-based epoxy coating liquid.
[0108] (2) Preparation of online coated BOPET film
[0109] The BOPET film in this embodiment is a typical three-layer co-extruded polyester film, wherein the A layer (upper surface layer) contains bright polyester chips, nano-SiO2 modified anti-sticking masterbatch and nano-CaCO3 modified anti-sticking masterbatch, wherein the mass fraction of the bright polyester chips is 60%, the mass fraction of the nano-SiO2 modified anti-sticking masterbatch is 20%, and the mass fraction of the nano-CaCO3 modified anti-sticking masterbatch is 20%; the B layer (core layer) is 100% bright polyester chips; the C layer (lower surface layer) contains bright polyester chips, nano-SiO2 modified anti-sticking masterbatch and nano-CaCO3 modified anti-sticking masterbatch, wherein the mass fraction of the bright polyester chips is 60%, the mass fraction of the nano-SiO2 modified anti-sticking masterbatch is 20%, and the mass fraction of the nano-CaCO3 modified anti-sticking masterbatch is 20%.
[0110] After pre-crystallization at 165°C, the raw material of layer B is sent to a fluidized bed and a drying tower for blast drying and impurity removal, and then enters a single-screw extruder 1, melted at 275°C, extruded onto a filter screen, and finally transported to a die head after metering by a melt pump; the raw material of layer A is directly sent to a single-screw extruder 2, melted and extruded at 280°C, and the melt is vacuum dried to remove moisture, and then transported to a die head after metering by a filter screen and a melt pump; layer C and layer A share a single-screw extruder 2, and are respectively transported to each surface layer at the die head through a diverter.
[0111] The melts of each layer are gathered at the die head to form a three-layer molten film sheet, which is slowly and evenly cast from the film lip. At the same time, under the action of 6.8kV high-voltage static electricity, it is tightly attached to the surface of a 29°C cold roller and cast into a thick polyester sheet.
[0112] The obtained thick sheet was passed to the longitudinal stretching section and longitudinally stretched under the conditions of preheating temperature of 85°C, stretching temperature of 101°C, and stretching ratio of 3.1. Then, the A and C sides of the export film were corona treated in turn, and then a uniform layer of water-based epoxy coating liquid was coated on both sides of the film through an anilox roller online coating device, with a coating amount of 2.5g / m on each side. 2Then the film enters the transverse stretching section and is transversely stretched under the conditions of preheating temperature 90°C, stretching temperature 105°C, setting temperature 225°C, and stretching ratio 3.2, and is cooled at 25°C to obtain a biaxially stretched polyester film.
[0113] The final formed film enters the traction section for flattening, thickness measurement, trimming and collection into a mother roll, and then is slit to produce the finished film.
[0114] Comparative Example 3
[0115] Comparative Example 3 describes a method for preparing a BOPET film for a composite current collector, and the specific steps include: (Compared with Example 1, the raw materials of the film A / C layer are changed)
[0116] (1) Preparation of water-based epoxy coating liquid
[0117] Add 20 parts by weight of water-based epoxy emulsion K-020 into a mixing tank, add 75 parts by weight of deionized water, stir at 500 rpm, and continue to add 2 parts by weight of water-based silica sol LS-50, 0.5 parts by weight of defoamer BW-225 and 0.5 parts by weight of leveling agent BW-404, continue stirring for 30 minutes, and finally add 2 parts by weight of curing agent K-62 and mix thoroughly to obtain a water-based epoxy coating liquid.
[0118] (2) Preparation of online coated BOPET film
[0119] The BOPET film in this embodiment is a typical three-layer co-extruded polyester film, wherein the A layer (upper surface layer) contains bright polyester chips, commercial anti-sticking masterbatch K and commercial anti-sticking masterbatch S, wherein the mass fraction of the bright polyester chips is 60%, the mass fraction of the commercial anti-sticking masterbatch K is 20%, and the mass fraction of the commercial anti-sticking masterbatch S is 20%; the B layer (core layer) contains graphene-modified bright polyester chips ①; the C layer (lower surface layer) contains bright polyester chips, commercial anti-sticking masterbatch K and commercial anti-sticking masterbatch S, wherein the mass fraction of the bright polyester chips is 60%, the mass fraction of the commercial anti-sticking masterbatch K is 20%, and the mass fraction of the commercial anti-sticking masterbatch S is 20%.
[0120] After pre-crystallization at 165°C, the raw material of layer B is sent to a fluidized bed and a drying tower for blast drying and impurity removal, and then enters a single-screw extruder 1, melted at 275°C, extruded onto a filter screen, and finally transported to a die head after metering by a melt pump; the raw material of layer A is directly sent to a single-screw extruder 2, melted and extruded at 280°C, and the melt is vacuum dried to remove moisture, and then transported to a die head after metering by a filter screen and a melt pump; layer C and layer A share a single-screw extruder 2, and are respectively transported to each surface layer at the die head through a diverter.
[0121] The melts of each layer are gathered at the die head to form a three-layer molten film sheet, which is slowly and evenly cast from the film lip. At the same time, under the action of 6.8kV high-voltage static electricity, it is tightly attached to the surface of a 29°C cold roller and cast into a thick polyester sheet.
[0122] The obtained thick sheet was passed to the longitudinal stretching section and longitudinally stretched under the conditions of preheating temperature of 85°C, stretching temperature of 101°C, and stretching ratio of 3.1. Then, the A and C sides of the export film were corona treated in turn, and then a uniform layer of water-based epoxy coating liquid was coated on both sides of the film through an anilox roller online coating device, with a coating amount of 2.5g / m on each side. 2 Then the film enters the transverse stretching section and is transversely stretched under the conditions of preheating temperature 90°C, stretching temperature 105°C, setting temperature 225°C, and stretching ratio 3.2, and is cooled at 25°C to obtain a biaxially stretched polyester film.
[0123] The final formed film enters the traction section for flattening, thickness measurement, trimming and collection into a mother roll, and then is slit to produce the finished film.
[0124] Film performance test:
[0125] The finished films in Examples 1-7 and Comparative Examples 1-3 were subjected to performance tests, wherein the test items included biaxial tensile strength, Young's modulus, thermal shrinkage, resistivity, and electrolyte immersion. The specific test process is as follows:
[0126] Tensile strength / Young's modulus: Cut a strip sample with a length of 150mm and a width of 15mm from the film sample, and then clamp the short side of the sample with the upper and lower clamps of the tensile tester, with a clamp spacing of 100mm. Start the instrument, and stretch the sample at a set speed of 100mm / min until the sample breaks. Finally, read the tensile strength value and Young's modulus value of the test in the supporting analysis software. Test 3 groups in each of the horizontal and vertical directions of each film sample and take the average value.
[0127] Thermal shrinkage rate: Cut a strip sample with a length of 150 mm and a width of 20 mm from the film sample, and draw a mark at 25 mm on both ends, so that the distance between the marks is 100 mm. Then set the oven temperature to 150°C, and then place the sample flat in the oven. After heating for 30 minutes, take it out and cool it. Use a ruler to measure the distance between the marks at both ends, and calculate the thermal shrinkage rate of the sample. The calculation method is shown in formula (1). Test 3 groups of each film sample in the horizontal and vertical directions, and take the average value.
[0128]
[0129] Where: S is the thermal shrinkage, %;
[0130] L0 is the spacing between marking lines before heating, mm;
[0131] L1 is the marking line spacing after heating, mm.
[0132] Resistivity: Cut a 100mm×100mm square specimen from the film sample and connect them to the input terminal and high voltage terminal of the high resistance meter respectively. Then adjust the test voltage to 500V, measure and record the surface resistance of the specimen. Test three parallel groups of each film sample and take the average value.
[0133] Electrolyte immersion: Cut a 50mm×50mm square sample from the film sample and put it into a wide-mouth bottle, add 20mL of lithium hexafluorophosphate (LiPF6) electrolyte, cover the bottle with a stopper and seal the bottle mouth with a sealing film to isolate the air, then put it into a vacuum drying oven, evacuate the vacuum (equipment vacuum degree ~133pa), heat to 80℃, keep it for 7h, then take it out and observe the degree of corrosion on the film appearance.
[0134] The test results of Examples 1-7 and Comparative Examples 1-3 are as follows:
[0135]
[0136] Results and Analysis
[0137] According to the above test results, it can be seen that the surface of the film coated with the water-based epoxy anti-corrosion layer has good chemical inertness, and the corrosion resistance to the electrolyte at high temperature is significantly improved, which can better meet the use requirements of the manufactured battery cells under harsh working conditions; at the same time, it can be seen that mixing graphene into the core layer of the film can effectively reduce its resistivity, which not only helps to eliminate the adverse effects of static electricity in the film during the production process, but also enables the film itself to have a certain electron transmission function, making up for the defect of low electron transmission efficiency of the composite current collector battery cell; and the addition of the nano-functional masterbatch has further improved the mechanical properties of the film, and the corresponding thermal shrinkage rate has also been effectively controlled, indicating that the presence of nano-anti-stick particles can play a more positive role in the behavioral characteristics of the resin molecule stretching process; it is worth noting that when graphene is not added to the core layer, the mechanical properties of the film also decrease to a certain extent. Considering the high-strength structure of graphene itself, it may produce a special interface effect when blended with the resin molecules, which helps to improve the mechanical properties of the formed film.
[0138] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0139] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.
Claims
1. A BOPET film for a composite current collector, comprising, from top to bottom: An upper surface layer, a core layer and a lower surface layer; and also includes a water-based epoxy coating liquid coated on the upper and lower surfaces of the film; The upper surface layer comprises: bright polyester chips, nano-SiO2 modified anti-sticking masterbatch, nano-CaCO3 modified anti-sticking masterbatch; the raw materials of the core layer comprise: graphene modified bright polyester chips; the lower surface layer comprises: bright polyester chips, nano-SiO2 modified anti-sticking masterbatch, nano-CaCO3 modified anti-sticking masterbatch.
2. The BOPET film for the composite current collector according to claim 1, characterized in that: The graphene-modified high-gloss polyester slice comprises nanographene material and polyethylene terephthalate.
3. The BOPET film for the composite current collector according to claim 1, characterized in that: The nano-CaCO3 modified anti-sticking masterbatch comprises nano-CaCO3 particles, terephthalic acid, isophthalic acid and ethylene glycol.
4. The BOPET film for the composite current collector according to claim 1, characterized in that: The nano-SiO2 modified anti-sticking masterbatch comprises nano-SiO2 particles, terephthalic acid, isophthalic acid and ethylene glycol.
5. The BOPET film for the composite current collector according to claim 1, characterized in that: The mass fraction of the glossy polyester chips in the upper surface layer and the lower surface layer is 60%.
6. The BOPET film for composite current collector according to claim 1, characterized in that: The mass fraction of the nano-SiO2 modified anti-sticking masterbatch of the upper surface layer and the lower surface layer is 20%.
7. The BOPET film for the composite current collector according to claim 1, characterized in that: The mass fraction of the nano-CaCO3 modified anti-sticking masterbatch in the upper and lower surface layers is 20%.
8. The BOPET film for the composite current collector according to claim 1, characterized in that: The water-based epoxy coating liquid comprises water-based epoxy emulsion, water-based silica sol, a defoamer and a leveling agent.
9. A method for preparing a BOPET film for a composite current collector, characterized in that: The method comprises the following steps: Deionized water is added to the water-based epoxy emulsion, and the mixture is stirred. Meanwhile, water-based silica sol, defoamer and leveling agent are added thereto, and the mixture is stirred. Finally, a curing agent is added and mixed to obtain a water-based epoxy coating liquid. The core layer raw material is pre-crystallized, air-dried, impurity-removed, melted, extruded to the filter screen, and finally transported to the die head; the upper surface layer raw material is melted and extruded, and the melt is vacuum-dried at the same time, and then transported to the die head; the lower surface layer and the upper surface layer share a single screw extruder, and are transported to each surface layer at the die head through a splitter; The core layer, upper surface layer and lower surface layer melts are conveyed to the three-layer die head through the melt pipe and accurately measured by the melt pump, and then cast and attached to the surface of the cold roller under the action of static electricity to form a polyester thick sheet with an upper surface layer, a core layer and a lower surface layer; After the thick sheet is longitudinally stretched, it is subjected to double-sided corona treatment, and then the water-based epoxy coating liquid is coated on both sides of the film online, and then enters the transverse stretching section for preheating, stretching, shaping and cooling treatment in sequence; The final formed film enters the traction section for flattening, thickness measurement, trimming and collection into a mother roll, and then is slit to produce the finished film.
10. Use of the BOPET film for composite current collector according to any one of claims 1 to 8 or the BOPET film for composite current collector prepared by the preparation method according to claim 9 in manufacturing battery cells.
Citation Information
Patent Citations
BOPET (Biaxially Oriented Polyester Film) base film for photoresist dry film and preparation method of BOPET base film
CN107443842A
Aqueous functional coating material, preparation method therefor and application of aqueous functional coating material
CN110343449A
Nano-modified epoxy resin anticorrosive paint and preparation method thereof
CN110669408A
Polyester film for thermal dye sublimation transfer printing ribbon and preparation method of polyester film
CN113185808A
Low-roughness release film base film and preparation method thereof
CN113524848A